Tanggung Jawab Notaris terhadap Pembuatan Akta Otentik yang Didasari Surat Palsu - I Made Dwi Sanjaya; Ida Ayu Putu Widiati; Ni Ketut Sri Astiti (Warmadewa Press, 2020)
This study aims to determine the factors that lead to the making of authentic deeds based on fake letters by notaries and to find out the legal consequences for notaries related to making authentic deeds based on fake letters. This research uses the normative law research method. The results showed that an authentic deed based on a fake letter was a deed made illegally in front of the authorized public official, so that it looks like the original. Then, the factor that caused the making of an authentic deed based on a fake letter was the notary's ignorance that the letter made was fake. The perpetrator did not have good faith in making the authentic deed. Therefore, as a consequence to a Notary who is proven to have cooperated in making an authentic Deed based on a false letter, the deed made by the Notary will have proof of the deed under hand and will be null and void, and the notary may be subject to criminal penalties under the provisions of the article 263 and 266 Criminal Code